2015
DOI: 10.1007/s12291-015-0522-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Glucose Concentrations Interfere with Estimation of Electrolytes by Indirect Ion Selective Electrode Method

Abstract: The estimation of electrolytes like sodium (Na(+)), potassium (K(+)) and chloride (Cl(-)) using direct and indirect ion-selective electrodes (ISE) is a routine laboratory practice. Interferents like proteins, triglycerides, drugs etc. are known to affect the results. The present study was designed to look into the effect of increasing glucose concentrations on estimation of Na(+), K(+) and Cl(-) by direct and indirect ISE. Pooled sera was mixed with glucose stock solution (20 g/dL) prepared in normal saline to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The indirect potentiometric method was used to measure urinary sodium levels. A negative bias might be reported in case of higher amounts of glucose excreted in urine (Goyal et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The indirect potentiometric method was used to measure urinary sodium levels. A negative bias might be reported in case of higher amounts of glucose excreted in urine (Goyal et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of very high glucose concentrations on the measurement of sodium concentration with ISE methods need further studies. In samples with extremely high glucose concentrations, one study reported finding spuriously high sodium concentrations when the [Na] S was measured using a direct ISE, but not for an indirect ISE [ 130 ], while a second study reported spuriously high sodium concentrations measured with an indirect ISE, but not with a direct ISE [ 131 ].…”
Section: Clinical Conditions Associated With Pseudohyponatremiamentioning
confidence: 99%
“…111 The accuracy of such methods of serum electrolytes estimation has been validated in standard clinical laboratories. 111,112 However, due to the additional preanalytical ions, the ratio of ion to water in serum is altered erratically, leading to inaccurate evaluations when ions are measured indirectly, which are rare and due to a preanalytical error. Another example is vacutainer tubes containing a Na-based anticoagulant, such as Na-heparin, Na-fluoride, Na-citrate, or Na-EDTA, which can markedly elevate plasma Na levels.…”
Section: Ion-selective Electrodes (Ise) Techniquesmentioning
confidence: 99%
“…An advantage of diluting the sample is that the measured activity better approximates the concentration, and consequently, indirect ISE results match those obtained using the other biochemistry analysis 111 . The accuracy of such methods of serum electrolytes estimation has been validated in standard clinical laboratories 111,112 . However, due to the additional preanalytical ions, the ratio of ion to water in serum is altered erratically, leading to inaccurate evaluations when ions are measured indirectly, which are rare and due to a preanalytical error.…”
Section: Dehydration Assessment Techniquesmentioning
confidence: 99%